A combined systems and structural modeling approach repositions antibiotics for Mycoplasma genitalium. (December 2015) - Kazakiewicz, Denis; Karr, Jonathan R.; Langner, Karol M.; Plewczynski, Dariusz
Graphical abstract: Highlights: We combined systems and structural modeling to repurpose antibiotics for new hosts. We applied our novel approach to the infectious bacterium Mycoplasma genitalium . Our method suggests that thymidylate kinase is a good potential drug target. Our method suggests that piperidinylthymines are good potential lead compounds. Combined systems and structural modeling is a powerful tool for drug repositioning. Abstract: Bacteria are increasingly resistant to existing antibiotics, which target a narrow range of pathways. New methods are needed to identify targets, including repositioning targets among distantly related species. We developed a novel combination of systems and structural modeling and bioinformatics to reposition known antibiotics and targets to new species. We applied this approach to Mycoplasma genitalium, a common cause of urethritis. First, we used quantitative metabolic modeling to identify enzymes whose expression affects the cellular growth rate. Second, we searched the literature for inhibitors of homologs of the most fragile enzymes. Next, we used sequence alignment to assess that the binding site is shared by M. genitalium, but not by humans. Lastly, we used molecular docking to verify that the reported inhibitors preferentially interact with M. genitalium proteins over their human homologs. Thymidylate kinase was the top predicted target and piperidinylthymines were the top compounds. Further work is needed to experimentally validate piperidinylthymines. In summary, combined systems and structural modeling is a powerful tool for drug repositioning.